2007
DOI: 10.1002/pola.22293
|View full text |Cite
|
Sign up to set email alerts
|

Rapid additive‐free TEMPO‐mediated stable free radical polymerizations of styrene

Abstract: The stable free radical polymerization (SFRP) of styrene, initiated with benzoyl peroxide in the presence of TEMPO, under bulk conditions, is demonstrated to proceed rapidly without the need for any rate enhancing additives such as camphorsulfonic acid, 2‐fluoro‐1‐methyl pyridinium p‐toluenesulfonate, or acetic anhydride. Monomer conversions as high as 70% can be achieved in 5 h or less while maintaining polydispersity indexes of 1.15. These results stand in stark contrast to earlier reactions that required 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Ultimately, we have been able to synthesize a polymer having comparatively low molecular weight and a narrow molecular weight distribution by utilizing nitroxyl radical-mediated living radical polymerization (Figure 3). 11 To do so, comonomer 2 was subjected to copolymerization with styrene (1:10) at 123 °C for 4 hours in the presence of catalytic TEMPO and benzoyl peroxide initiator. Of note, further heating improves yield of the polymer but leads to the formation of partially insoluble polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, we have been able to synthesize a polymer having comparatively low molecular weight and a narrow molecular weight distribution by utilizing nitroxyl radical-mediated living radical polymerization (Figure 3). 11 To do so, comonomer 2 was subjected to copolymerization with styrene (1:10) at 123 °C for 4 hours in the presence of catalytic TEMPO and benzoyl peroxide initiator. Of note, further heating improves yield of the polymer but leads to the formation of partially insoluble polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Although at first glance the system seems relatively well studied, no detailed/reliable experimental results (over the whole range of polymerization) are available in the literature. For instance, the conversion versus time data points reported in the past only capture the first few hours of the experiment and low to medium conversion (see, e.g., Veregin et al, 1996a,b; Dollin et al, 2007). Average molecular weight data are usually not readily available (Veregin et al, 1996a,b) and, if available, are presented as number‐average molecular weight points evaluated at a limited number of conversion levels (usually, low‐medium‐high conversion; see, e.g., MacLeod et al 1997; Dollin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…60 An alternative to primary initiators are alkoxyamines, 33 -36 adducts of an initiator fragment (optional), a monomer, and a nitroxide (for example 3-5). The C-O bond of the alkoxyamine is labile and upon heating dissociates to form an initiating species and a stable radical mediator in a 1 : 1 ratio, although this is not necessarily the right ratio of the propagating chain to nitroxide for a well controlled polymerization.…”
Section: Unimolecular Initiatorsmentioning
confidence: 99%
“…82 It was subsequently shown that polymerizations of styrene can proceed quickly and efficiently using a primary initiator, such as BPO, in the absence of an additive, if the ratio of TEMPO to BPO is varied according to the targeted molecular weight. 60 …”
Section: Rate Enhancement Of Stable Free Radical Polymerization Throumentioning
confidence: 99%